STUDY OF THE INFLUENCE OF THE POWER OF TRUCK FLOWS ON THE INDICATORS OF THE FORMATION PLAN TRAINS - Kuzmenko, A. I; Bekh, P. V; Lashkov, O. V; Maksymenkov, E. A. (Systems and Technologies, 2023)
The level of competitiveness and attractiveness of railways in the market of transport services largely depends on the quality of work of railway stations. In modern economic conditions, one of the main factors of ensuring high efficiency of the operational work of railways is the minimization of the time spent by cars at stations. For this purpose, the stations must have a sufficient reserve of throughput and processing capacity to cover peak loads. On the other hand, it is necessary to minimize the own costs of the stations, reducing the excess technical potential. As you know, the efficiency of the station’s operation is determined by the level of its technical equipment, work technology and control system. In this connection, the problem of effective technical and economic management of stations becomes particularly relevant, the main task of which is to make economically justified decisions both in operational management and in planning organizational and technical measures aimed at increasing the efficiency of station operation. The main volume of car traffic processing is carried out at sorting stations. The execution of the transportation plan, the most important indicators of freight traffic, depends on their successful work. Therefore, it is worth developing measures to improve the design and technology of the existing stations. Among such measures, it is possible to single out reconstructive measures aimed at changing the design of stations, and organizational ones, which involve improving the technological process and the station management system. The need to rebuild the sorting station or improve the technology of its operation can be caused by various reasons, such as a change in the volume and structure of traffic flows, electrification of lines on approaches, organization of high-speed traffic, construction of second main tracks, connection of new access tracks, etc. The number of options for further comparison and evaluation can be quite large in some cases. Therefore, when choosing competitive options, practical experience already accumulated by design engineers is of great importance, which helps to select only those options that most fully and effectively meet the given task. As a criterion for evaluating each of the intended options, the most often used are the costs associated with the implementation of a set of measures corresponding to the option. This indicator is the most universal, but at the same time it does not take into account many factors that significantly affect the choice of option (ensuring traffic safety, labor protection, etc.). The choice of the most rational complex of reconstructive or organizational measures for each specific station is a rather difficult task due to the impossibility of conducting experiments on real objects to evaluate the intended options. When evaluating one or another option, it is necessary to forecast the performance indicators of the station after the implementation of the set of measures provided for by this option. At the same time, the complexity of the technological processes of the operation of railway stations makes it impossible to use direct analytical dependencies of the form Y=F(X) for these purposes. In addition, it is necessary to take into account that the performance indicators of the stations are significantly influenced by the dispatching control system, i.e. the operational and dispatching personnel of the stations.